2018
DOI: 10.1002/bab.1702
|View full text |Cite
|
Sign up to set email alerts
|

Improved activity of α‐L‐arabinofuranosidase from Geobacillus vulcani GS90 by directed evolution: Investigation on thermal and alkaline stability

Abstract: α-L-Arabinofuranosidase (Abf) is a potential enzyme because of its synergistic effect with other hemicellulases in agro-industrial field. In this study, directed evolution was applied to Abf from Geobacillus vulcani GS90 (GvAbf) using one round error-prone PCR and constructed a library of 73 enzyme variants of GvAbf. The activity screening of the enzyme variants was performed on soluble protein extracts using p-nitrophenyl α-L-arabinofuranoside as substrate. Two high activity displaying variants (GvAbf L307S a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 38 publications
5
23
0
Order By: Relevance
“…shown that its growth conditions are in a range of 37-72°C and pH 5.5-9 and it is optimally grown at 60°C and pH 6 (Caccamo et al, 2000). In addition, it has been reported that the strain 3S-1 is phylogenetically the closest strain to the strain GS90 (Sürmeli et al, 2019) used in this study as a xylanase producer source (GvXyl-producer strain). Another strain G. vulcani PSS1 obtained from the gut microbiome of healthy Japanese approximately has 3.4 mb genome (GeneBank ID: JPOI01000001.1) (Nishijima et al, 2016).…”
Section: Re Sults and Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…shown that its growth conditions are in a range of 37-72°C and pH 5.5-9 and it is optimally grown at 60°C and pH 6 (Caccamo et al, 2000). In addition, it has been reported that the strain 3S-1 is phylogenetically the closest strain to the strain GS90 (Sürmeli et al, 2019) used in this study as a xylanase producer source (GvXyl-producer strain). Another strain G. vulcani PSS1 obtained from the gut microbiome of healthy Japanese approximately has 3.4 mb genome (GeneBank ID: JPOI01000001.1) (Nishijima et al, 2016).…”
Section: Re Sults and Discussionmentioning
confidence: 85%
“…Another strain G. vulcani PSS1 obtained from the gut microbiome of healthy Japanese approximately has 3.4 mb genome (GeneBank ID: JPOI01000001.1) (Nishijima et al, 2016). Some portion of the genome shares a 99.74% identity with 16S rRNA gene sequence of GvXyl-producer strain GS90 (GeneBank ID: MT611101.1) (Nishijima et al, 2016;Sürmeli et al, 2019) (Supporting Information). Additionally, the strain PSS1 genome encodes endo-1,4-beta-xylanase amino acid sequence of 407 residues and another xylanolytic enzyme alpha-N-arabinofuranosidase of 500 residues, deposited in the NCBI as WP_033842342.1 and WP_202807098.1 accession numbers, respectively (https://www.ncbi.nlm.nih.gov) (Nishijima et al, 2016).…”
Section: Re Sults and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L8S may have in uenced the 3D structure of the GH because leucine is relatively and non-polar amino acid, whereas serine is smaller and more polar amino acid (Probst et al, 2013). In literature, some studies have been reported on the replacement of the leucine with serine amino acid which causes a signi cant result, thereby probably signi cant change of the 3D structure of the proteins (Probst et al, 2013;Sürmeli et al, 2019Sürmeli et al, , 2022. Therefore, variation depending on its new function may be eliminated from the population in the next generations.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure and active site residues of PTE are well-known (Figure ). In efforts to evolve PTE for V-agent hydrolysis, the most commonly targeted active site residues include Ile106, Phe132, His254, His257, Ser308, and a residue from an adjacent loop, Ile274. , Enzymatic evolution experiments are often presented as straightforward, showing a linear increase in activity from a starting variant to a more “evolved” variant with enhanced catalytic activity or stability. ,, However, the actual complexity of the problem is relatively immense. As demonstrated by the sequence similarity networks (SSNs) presented in Figure , the complexity of the evolution process increases exponentially as more sites are included.…”
mentioning
confidence: 99%